2023
DOI: 10.1108/jedt-07-2022-0354
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the key factors of operating environment for small and medium contractors in the developing economies: the case of Ethiopia

Abstract: Purpose Small and medium contractors (SMCs) play a significant role in socioeconomic development. Their strong links with other sectors of the economy have a multiplier effect on any country’s growth. However, the construction business, especially for SMCs, is not an easy business as several roadblocks affect their sustenance. This study aims to examine the factors affecting the sustainable competency of SMCs emerging from the business environment in which the Ethiopian construction industry (CI) operates. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…However, several studies indicated that time spent on management in small construction projects was disproportionate to project costs (Amoah and Pretorius, 2020)). Moreover, due to a lack of internal experience, small and medium-sized contractors (SMCs) are not effective in managing risks in their small projects (Aboneh and Mahesh, 2023). There is a dearth of research on the implementation of RM in small projects.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies indicated that time spent on management in small construction projects was disproportionate to project costs (Amoah and Pretorius, 2020)). Moreover, due to a lack of internal experience, small and medium-sized contractors (SMCs) are not effective in managing risks in their small projects (Aboneh and Mahesh, 2023). There is a dearth of research on the implementation of RM in small projects.…”
Section: Introductionmentioning
confidence: 99%